АЎЫЗЕКИ ӘДЕБИЯТ ҲӘМ АДАМЗАТ ТӘРБИЯСЫ - Пазылов, Т.А. (FAN va JAMIYAT, 2020)
The article is devoted to the role of folklore in the formation, development, upbringing and development of mankind, as well as the views of some researchers on these issues.